Mobile money services and the growth of the Jua Kali enterprises in Makueni county - Mutie, Mutua Daniel; Kiweu, Josephat M.; Mwasa, Daniel (Journal of Accounting, Business and Finance Research, 2025)
This study investigated the influence of mobile money transfer on the growth of Jua Kali enterprises in Makueni County, Kenya. Mobile money platforms such as M-Pesa have become integral to informal sector businesses, enabling faster, safer, and more convenient financial transactions while expanding access to credit and savings. Using a correlational research design, primary data were collected from a stratified sample of 342 Jua Kali entrepreneurs, with 266 valid responses analyzed through descriptive statistics and multiple regression. Results show that 76.7% of respondents received more than half of their business revenue via mobile money, with a mean perceived sales improvement score of 3.93 on a five-point scale. Regression analysis revealed a significant positive relationship between mobile money usage and enterprise growth (B = 0.470, p < 0.001), confirming that greater integration of mobile money into business operations enhances revenue performance. The findings highlight mobile money as a key driver of financial inclusion and growth within Kenya’s informal sector, aligning with the Technology Acceptance Model and Financial Inclusion Theory. The study recommends expanding digital infrastructure, reducing transaction costs, and providing targeted training to help entrepreneurs maximize mobile money benefits. These insights contribute to policy and practice aimed at strengthening the resilience and competitiveness of Jua Kali enterprises.